The endoscopy profile of patients with Gastrointestinal Bleeding (GIB) at Klungkung Regional General Hospital, Bali, Indonesia during the 2014-2018 period - I Gede Restu Mahendra Sugiarta; I Ketut Sumandi (Intisari Sains Medis, 2020)
Background: Gastrointestinal Bleeding (GIB) is an emergency case that often found in the condition. In Indonesia, the prevalence of GIB in the population is still unknown. Endoscopy is an examination procedure that used to see abnormalities in gastrointestinal mucosa or lumen of GIT, which is a relatively safe procedure to determine the causal of GIB. This study aims to evaluate the endoscopy profile of patients with GIB at Klungkung Regional General Hospital, Bali, Indonesia during the 2014-2018 periodMethods: A descriptive cross-sectional study was conducted among the medical records of 410 patient’s register who underwent endoscopy due to GIB during 2014-2018 period using total sampling technique at Klungkung Regional General Hospital, Bali, Indonesia. Variables assessed in this study included the sociodemographic of patients, type of endoscopy, and the outcome of endoscopy procedure. Data were analyzed using SPSS version 21 for Windows.Results: The highest proportion based on age were in the age of 51-60 years-old (23.4%) group. Males were predominant in this study (57.1%) compared with females (42.9%). Based on the type of endoscopy, Esophagogastroduodenoscopy (EGD) examination was predominant (80.7%) compared with colonoscopy (19.3%). Superficial Gastritis was the most common findings (41.5%) from EGD, while colorectal tumours with suspected colorectal cancer and haemorrhoid (6.1%) were predominant in colonoscopy evaluation.Conclusion: The endoscopy profile found among patients with GIB at Klungkung Regional General Hospital, Bali, Indonesia was dominated by age 51-60 years-old group, males gender, EGD assessment, superficial Gastritis in EGD, and colorectal tumour in colonoscopy evaluation.